2022
DOI: 10.3390/jpm12060925
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Autoimmune Liver Diseases: Relevant Aspects in Clinical Practice

Abstract: Autoimmune liver diseases (AILDs) include autoimmune hepatitis, primary biliary cholangitis and primary sclerosing cholangitis. The etiologies of AILD are not well understood but appear to involve a combination of genetic and environmental factors. AILDs commonly affect young individuals and are characterized by a highly variable clinical course. These diseases significantly influence quality of life and can progress toward liver decompensation or the onset of hepatocellular or cholangiocarcinoma; a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 124 publications
3
13
0
1
Order By: Relevance
“…The interaction between sexes in general LT studies has been shown to affect post-transplant results, particularly in graft survival [23]. However, no studies have been conducted to determine the relationship between donor and recipient sexes after LT in patients with PSC, where sex is known to play a role in the epidemiology of this disease [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between sexes in general LT studies has been shown to affect post-transplant results, particularly in graft survival [23]. However, no studies have been conducted to determine the relationship between donor and recipient sexes after LT in patients with PSC, where sex is known to play a role in the epidemiology of this disease [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several non-PSC liver transplant studies have identified recipient-donor sex mismatch to confer a modified risk to post-LT prognosis, potentiating early demise of grafted livers and causing intrinsic graft complications [15,16]. Given that PSC has been associated with differential prognostic and disease-development patterns based on sex [17,18], it is essential to investigate the differences in post-LT prognosis due to sex differences or sex mismatch between recipients and donors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely recognized clinical characteristics of PBC is a strong female preponderance. 37 Multiple studies showed that male gender is associated with a delay in diagnosis and, as a result, an increased age at PBC identification. [37][38][39] Multiple studies have shown that fatigue is more likely to be associated with female sex at the time of PBC presentation.…”
Section: Natural Historymentioning
confidence: 99%
“…37 Multiple studies showed that male gender is associated with a delay in diagnosis and, as a result, an increased age at PBC identification. [37][38][39] Multiple studies have shown that fatigue is more likely to be associated with female sex at the time of PBC presentation. 37 Additionally, several studies demonstrated that an inadequate response to UDCA is more prevalent in males than in females.…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation